2014
DOI: 10.3389/fmicb.2014.00109
|View full text |Cite
|
Sign up to set email alerts
|

Phototrophic biofilm assembly in microbial-mat-derived unicyanobacterial consortia: model systems for the study of autotroph-heterotroph interactions

Abstract: Microbial autotroph-heterotroph interactions influence biogeochemical cycles on a global scale, but the diversity and complexity of natural systems and their intractability to in situ manipulation make it challenging to elucidate the principles governing these interactions. The study of assembling phototrophic biofilm communities provides a robust means to identify such interactions and evaluate their contributions to the recruitment and maintenance of phylogenetic and functional diversity over time. To examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
136
1
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(153 citation statements)
references
References 102 publications
(132 reference statements)
9
136
1
4
Order By: Relevance
“…Interestingly, this cyanobacterium is known to be motile and metabolically coupled to heterotrophic bacteria that match or are very similar to the OTUs abundant near the surface of the mat, for example, Roseibacterium sp. HL7711_P4H5 (Cole et al, 2014;Nelson et al, 2016). The most abundant OTU identified in this system belonged to a cyanobacterium of the family Pseudanabaenaceae.…”
Section: Specific Taxa and Biological Nichesmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, this cyanobacterium is known to be motile and metabolically coupled to heterotrophic bacteria that match or are very similar to the OTUs abundant near the surface of the mat, for example, Roseibacterium sp. HL7711_P4H5 (Cole et al, 2014;Nelson et al, 2016). The most abundant OTU identified in this system belonged to a cyanobacterium of the family Pseudanabaenaceae.…”
Section: Specific Taxa and Biological Nichesmentioning
confidence: 99%
“…These niche spaces mapped to common taxa that were associated with measured variance in community structure (beta diversity shown in Figure 4). Some OTUs, belonging to the most abundant families (Supplementary Figure S5), matched species that have been previously described and sequenced (Cole et al, 2014;Nelson et al, 2016) allowing function, relating to microbial lifestyle and niche space, to be inferred. The Phormidium sp.…”
Section: Specific Taxa and Biological Nichesmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, we and others have observed that such mixed communities have heightened tolerance to antimicrobials, chemical stress and predation (Burmolle et al ., 2006; Lee et al ., 2014; Kumar and Ting, 2015). Additional models allow for studies of autotroph–heterotroph interactions (Elenter et al ., 2007; Cole et al ., 2014), metabolic cooperation to degrade xenobiotics (Christensen et al ., 2002) and cooperation and competition between different species (Foster and Bell, 2012; Fiegna et al ., 2015), as examples of biofilm community interactions recently explored.…”
mentioning
confidence: 99%